Quality of Pharmaceutical Services on Patient Loyalty of RSUD Soewandhie Surabaya - Ira Purbosari; Intan Ayu Kusuma Pramushinta; Asri Wido Mukti; Dian Viciennsia Sigalingging (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Quality of health services is an important thing. The level of perfection of a service to increase patient satisfaction. The quality of patient care is very influential on loyalty. The purpose of this study was to assess the quality of medical services at pharmaceutical facilities and patient retention at RSUD Dr. Mohamad Soewandhie and saw the relationship between the quality of health services and the loyalty of BPJS and non-BPJS patients. This research is a descriptive research with a survey method using a questionnaire to 150 respondents who meet the research inclusion criteria. The research instrument used was a closed questionnaire with a total of 19 questions. Furthermore, the data obtained were analyzed descriptively, and then the Chi-square test was carried out to determine the relationship between research variables. The results of this study are included in the good category for service quality, with the percentage of respondents who answered at 53.3% and loyalty at 65.3%. There is a significant relationship between the quality of pharmacy installation services and patient loyalty